Desenvolvimento de um serviço de informações gamificado como uma estratégia de engajamento do consumidor com a marca - Miozzo, Regina Kossmann (Universidade do Vale do Rio dos Sinos, 2015)
Gamification is a growing phenomenon that concerns both researchers and practitioners. Game elements have been applied in several contexts and activities out of entertainment with the aim of enriching the experiences of those who execute them, generating higher levels of interest, involvement, entertainment and engagement. Gamification has been suggested, especially by IT industry, as a marketing strategy to develop consumer engagement. However, there is no empirical research related to the use of gamification to promote engagement in utilitarian brands consumers such as agricultural machinery. The present study aims to analyze which aspects of gamification can develop the involvement of the agricultural machinery consumer in an interactive digital experience, identifying the most relevant elements on encouraging consumer brand engagement behaviors. The research adopts a qualitative approach, adopting the Design Science Research (DSR) as the research method. DSR was applied to the development of a technological artifact which was presented and evaluated by agricultural machinery consumers. In order to get empirical data, the study was performed into a company that develops, produces and commercializes agricultural machinery, involving marketing, IT and after sales professionals, and Brazilian agricultural machinery consumers. The activities performed comprehended semi structured interviews and questionnaires that aimed to understand the problem to be addressed to identify the company´s motivation to find a solution and to get subsidies to design the artifact. Data was collected to design and implement a medium fidelity prototype of the proposed artifact. The prototype was used and evaluated by consumers in order to verify gamification's potential on the involvement development and consequent engagement intentions. The main results indicate gamification does have the potential to develop the involvement of agricultural machinery consumers. However, there are element and risks to be considered, especially the ones related to the consumer's interests and motivations. Three perspectives were identified, by which the generation of value through gamification can be driven towards the brand engagement: utility, pleasure and social relationship. This research contributes to the enrichment of the gamification literature, adding empirical study about its usage in marketing context and also demonstrating the usage of a method to implement gamification in a solution to stimulate consumer involvement and engagement behavior intention.
Keywords: Gamificação; Marketing; Envolvimento; Engajamento do consumidor com a marca; Design science research; Gamification; Marketing; Involvement; Consumer brand engagement; ACCNPQ::Ciências Sociais Aplicadas::Administração